2012
DOI: 10.3856/vol40-issue3-fulltext-13
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth changes and population dynamics of the black pomfret (Parastromateus niger) and the frigate tuna (Auxis thazard thazard), in the Taiwan Strait

Abstract: With five age groups of each, the dominant black pomfret was one year, while frigate tuna was two years. The total mortality coefficient (Z) and the fishing mortality (F) of the black pomfret were at high levels, the exploitation ratio (E) was over 0.5, and the number of captured juvenile fishes showed that the stock of black pomfret in this area was overexploited and improper fishing gear was utilized.Compared with previous studies, the maximum and mean fork length, body weight and age of the two fishes decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…The results of these two studies indicated that the species had the growth rate higher than 0.5 year -1 . The growth rate of P. niger in Taiwan Strait and West Coast of India were 0.3157 year -1 and 0.73 year -1 , respectively (Tao et al 2012;Khan et al 1992). The age of P. niger in Iranian Coast of Oman Sea was determined at the age 1 to 6-year-old fish based on otolith cross sections (Yadollahvand and Rahnama 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results of these two studies indicated that the species had the growth rate higher than 0.5 year -1 . The growth rate of P. niger in Taiwan Strait and West Coast of India were 0.3157 year -1 and 0.73 year -1 , respectively (Tao et al 2012;Khan et al 1992). The age of P. niger in Iranian Coast of Oman Sea was determined at the age 1 to 6-year-old fish based on otolith cross sections (Yadollahvand and Rahnama 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specific ecological factors, such as population density, environment temperature, and prey density, may cause growth parameters for the two species to vary in different sea areas. Compared with previous studies in the Taiwan Strait (Zhang, 1987;Lu et al, 1999a,b), the population structures (Table 3) and ecological characteristics (Table 5) of these two species have changed in recent decades, indicated that the populations of the two species were younger, smaller and earlier in sexual maturity, similar to that of other demersal fishes such as the little yellow croaker Larimichthys polyactis (Bleeker, 1877) (Chen et al, 2010), black pomfret Parastromateus niger (Bloch, 1795), and the bullet mackerel Auxis thazard thazard (Lac ep ede, 1800) (Tao et al, 2012) in the north-central Taiwan Strait.…”
Section: Discussionmentioning
confidence: 78%
“…Meanwhile, coastal and offshore catches have decreased from 408,000 t in 1980 to 198,000 t in 2018 (Fisheries Agency, 1949-2019; Figure 2). Among the other stocks affected were P. anomala (Du et al, 2010), P. argentata (Ju et al, 2016), P. macracanthus (Ju et al, 2016), and P. niger (Tao et al, 2012), occurring in the western Taiwan waters (Taiwan Strait), and which became overfished by the 2000s. These fish species belong to Taiwan's most important economic species.…”
Section: Discussionmentioning
confidence: 99%